2019
DOI: 10.1074/jbc.ra118.006106
|View full text |Cite
|
Sign up to set email alerts
|

Retinal degeneration 3 (RD3) protein, a retinal guanylyl cyclase regulator, forms a monomeric and elongated four-helix bundle

Abstract: Retinal degeneration 3 (RD3) protein promotes accumulation of retinal membrane guanylyl cyclase (RetGC) in the photoreceptor outer segment and suppresses RetGC activation by guanylyl cyclase-activating proteins (GCAPs). Mutations truncating RD3 cause severe congenital blindness by preventing the inhibitory binding of RD3 to the cyclase. The high propensity of RD3 to aggregate in solution has prevented structural analysis. Here, we produced a highly soluble variant of human RD3 (residues 18 -160) that is monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 50 publications
(107 reference statements)
1
47
0
Order By: Relevance
“…Currently little is known about the mechanisms of RD3 interaction with the cyclase. The structures of GCAPs (30 -32) and recently RD3 (33) have been established; however, the structure of the cyclase itself still presents a major barrier for understanding the molecular dynamics of the complex. To date, the threedimensional structure of RetGC has been resolved only for its catalytic core (34,35), not for those domains that present most important regulatory parts.…”
Section: Mechanism Of Rd3 Retinal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently little is known about the mechanisms of RD3 interaction with the cyclase. The structures of GCAPs (30 -32) and recently RD3 (33) have been established; however, the structure of the cyclase itself still presents a major barrier for understanding the molecular dynamics of the complex. To date, the threedimensional structure of RetGC has been resolved only for its catalytic core (34,35), not for those domains that present most important regulatory parts.…”
Section: Mechanism Of Rd3 Retinal Degenerationmentioning
confidence: 99%
“…RD3 and GCAP (11,17) not only have highly dissimilar protein sequences (Ͻ5% overall identity and Ͻ9% similarity in pairwise alignment; European Bioinformatics Institute EMBOS Needle on-line tool) but also drastically dissimilar three-dimensional structures. The guanylyl cyclasebinding interface on RD3 (22,33) occupies the central part of RD3 elongated bundle of ␣-helices, whereas the cyclase-binding interface of GCAP occupies portions of three helix-loophelix EF-hand domains (38). This suggests that most likely the binding sites for RD3 and GCAP on RetGC are also nonidentical.…”
Section: Mechanism Of Rd3 Retinal Degenerationmentioning
confidence: 99%
“…The molecular structure of RetGC remains largely unknown and mutational analysis of the cyclase presents a major challenge because of the larger size of the enzyme and the complexity of its regulation. Another major challenge presents high propensity of RD3 to precipitate at concentrations required for structural analyses ( 24 , 27 ). However, the three-dimensional structure of RD3 core, an elongated bundle of four α-helices ( Fig.…”
mentioning
confidence: 99%
“…However, the three-dimensional structure of RD3 core, an elongated bundle of four α-helices ( Fig. 1 ), was recently established using a soluble variant of RD3 that retained attenuated affinity for the cyclase ( 27 ). The preliminary testing of several fragments in RD3 primary structure that contained surface-exposed and buried in the core structure residues indicated that the cyclase-binding interface on RD3 includes the central portion of the helical bundle ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation